2012
DOI: 10.1097/mph.0b013e3182677fc6
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Interleukin-6 (IL-6) and C-reactive Protein (CRP) in Children and Young Adults With Febrile Neutropenia During Chemotherapy for Cancer

Abstract: Low level of IL-6 may help differentiate patients with FUO from those with documented infections. A rising CRP is indicative of serious infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…CRP was the most frequently studied host biomarker in this review and the majority of these studies (33/36; 92%) reported statistically significant differences in CRP levels measured in patients with bacterial and those with non-bacterial infections ( Table 2 ) [ 20 , 22 24 , 26 , 28 32 , 34 38 , 40 42 , 44 , 46 50 , 52 62 ]. Half of the studies (18/36; 47%) reported sensitivity and specificity at ranges of 61.2%-100% and 26%-100% respectively to identify bacterial infections [ 20 , 22 24 , 26 , 28 , 29 , 31 , 34 , 37 , 40 , 42 , 48 , 50 , 53 , 56 , 58 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…CRP was the most frequently studied host biomarker in this review and the majority of these studies (33/36; 92%) reported statistically significant differences in CRP levels measured in patients with bacterial and those with non-bacterial infections ( Table 2 ) [ 20 , 22 24 , 26 , 28 32 , 34 38 , 40 42 , 44 , 46 50 , 52 62 ]. Half of the studies (18/36; 47%) reported sensitivity and specificity at ranges of 61.2%-100% and 26%-100% respectively to identify bacterial infections [ 20 , 22 24 , 26 , 28 , 29 , 31 , 34 , 37 , 40 , 42 , 48 , 50 , 53 , 56 , 58 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study, PCT and IL-6 were both significant independent predictors of severe sepsis and were superior to CRP 60 . More studies have been published in pediatric patients with suspected sepsis which concluded that IL-6 levels might be helpful for the diagnosis of sepsis 61 - 65 . However, a conclusive study with large sample size is also missing for this patient population.…”
Section: Biomarkersmentioning
confidence: 90%
“…In studies in which CRP levels were evaluated by focus of infection in febrile neutropenia, Fleischhack et al (34) found that CRP levels were significantly higher in subjects with Gram-negative bacteremia compared with the FUO group, and similar to the subjects with CDIs. Chaudhary et al (35) found that CRP values on the first day of febrile neutropenia did not show a difference between groups, but were significantly higher on the third day in MDIs compared with the other groups. Tezcan et al (27) could show no difference between MDIs and microbiologically unconfirmed infections in terms of CRP levels.…”
Section: Discussionmentioning
confidence: 99%